Parametric effects on composite floor systems under column removal scenario - Fu, Qiu Ni (2021)
This paper presents parametric studies on three-dimensional steel-frame-composite-floor systems (3D composite floor systems) subjected to column loss using macro-based finite element (FE) models and a verified analytical method. The FE modelling method is verified by four actual experimental tests with three important variables, viz. slab aspect ratio, boundary condition and degree of composite action between composite slabs and steel beams. To overcome the shortage of data acquisition in the actual composite floor system tests, the FE models can be used to investigate the effects of these variables on load-resisting mechanisms, such as flexure and catenary action in the double-span girder and the double-span beam over the missing column, and flexure and tensile membrane action in composite slabs. In addition, the parametric studies are extended to include slab thickness. In a similar manner, the analytical model is used to study the effects of slab aspect ratio and joint type on robustness of 3D composite floor systems. After evaluating the robustness of eight sub-structures with different combinations of extended-end-plate, flush-end-plate, web-cleat and fin-plate joints, a few combinations are recommended. Lastly, consistency between FE simulations and the analytical predictions is confirmed through a comparison of energy stored in different structural members.